Assessing the Impact of Message Sources and Content on B2B Social Media Marketing Effectiveness - Nanik Hariyana,; Nurkholish Majid,; Yuniningsih, (Communication Today, 2025)
A B2B company’s success in interacting with customers on social media depends mainly on its messaging strategy. In this research, we use a new method to investigate the origins of influential messages and content in the social media domain. To investigate these dynamics, we conducted four experiments to test our proposed relationships. The research results show a significant finding: Employee-generated content performs better than content created by the company when it comes to driving social media engagement. We identify two essential mechanisms underlying this phenomenon. Trust can be founded on content or on engagement. This mechanism explains how message source impacts social media engagement. Furthermore, our observations revealed that employee-generated messages, especially those using emojis, had a more significant impact on customer engagement compared to company-generated messages alone. The inclusion of emojis plays an essential role in this dynamic. Finally, our findings demonstrate the benefit of including objective facts in social media posts to boost customer engagement. This finding has significant implications for B2B marketers, underscoring the importance of selecting suitable sources for social media messages to optimise engagement.